(untitled) (Terr@ Plural, 2019)
The full constitution of housing territories that provide adequate living conditions, sometimes precarious due to factors that hinder the appropriation and usage of space, such as insufficient infrastructure and essential services, urban location segregated, legal uncertainty, social tension, as well as environmental characteristics that pose risks to residential occupation. In this paper, we discuss the factors related to territorial precariousness in the urban spaces regarding housing. As an empirical study, we present an analysis of six precarious territories in the mid-sized city of Chapecó that has stood out for its economic growth and intense urbanization, but with outstanding remarkable sociospatial inequalities.